New records of Dictyopsocus pennicornis (Burmeister) (Psocodea 'Psocoptera': Psocidae: Psocinae) - Oliveira, João Alves; Silva-Neto, Alberto Moreira; Mello Mendes, Diego Matheus; García Aldrete, Alfonso Neri (EntomoBrasilis, 2017)
Abstract. First records of Dictyopsocus pennicornis (Burmeister), in the northeastern Brazilian states of Bahia, Ceará and Paraíba, are presented, with biogeographic comments. Novos registros de Dictyopsocus pennicornis (Burmeister) (Psocodea 'Psocoptera': Psocidae: Psocinae) Resumo. Os primeiros registros de Dictyopsocus pennicornis (Burmeister), nos estados brasileiros da Bahia, Ceará e Paraíba são apresentados, com comentários biogeográficos.